Asian hornet Vespa velutina nigrithorax venom: Evaluation and identification of the bioactive compound responsible for human keratinocyte protection against oxidative stress. (March 2020) - LE, Thao Nhi; Da Silva, David; Colas, Cyril; Darrouzet, Eric; Baril, Patrick; Leseurre, Lucie; Maunit, Benoît
Abstract: The present study aimed to explore the potential antioxidant molecules of the Asian hornet venom ( Vespa velutina nigrithorax ) responsible for radical scavenging activity and human keratinocyte protection against oxidative stress. We developed a first technical platform that combined a DPPH radical scavenging chemical assay and cytotoxicity and ROS (reactive oxygen species) production in HaCaT keratinocyte cells exposed to UVB to evaluate the antioxidant property of V. velutina venom. We further employed Thin Layer Chromatography (TLC) combined with the DPPH assay as a targeted separation approach to isolate the antioxidant compounds responsible for the free radical scavenging property of V. velutina venom. In parallel, the latter was fractionated by a HPLC-DAD non-targeted separation approach. From this experiment, nine fractions were generated which were again evaluated separately for their antioxidant properties using DPPH assays. Results showed that only one fraction exhibited significant antioxidant activity in which serotonin was identified as the major compound by a UHPLC-ESI-QTOF HRMS/MS approach. We finally demonstrated, using purified serotonin molecule that this bioactive structure is mostly responsible for the free radical scavenging property of the crude venom as evidenced by DPPH and ROS assays in HaCaT cells exposed to UVB. Graphical abstract: Image 1 Highlights: Potential antioxidant property of V. velutina venom was evaluated by ROS assay in keratinocytes. Antioxidant compound was isolated by TLC-DPPH and HPLC-DAD using DPPH assay. Serotonin was identified as the main antioxidant in venom by UHPLC-ESI-QTOF HRMS/MS.